Acute pancreatitis complicating Crohn's disease: mere coincidence or causality?. Issue 9 (September 1992) - Tromm, A; Hüppe, D; Micklefield, G H; Schwegler, U; May, B
Abstract : An example of acute pancreatitis developing five weeks after initial treatment with 5-aminosalicylic acid (5-ASA) and methylprednisolone for severe Crohn's disease is reported in a 37 year old female patient. She had undergone cholecystectomy for gall stones some years earlier. There was no evidence of acute or chronic pancreatitis. No morphological changes of the upper gastrointestinal tract were found except for some irregularity of the main pancreatic duct and the secondary ducts on endoscopic retrograde pancreatography. Rechallenge with 5-ASA did not induce recurrent pancreatitis or changes in pancreatic enzymes. This case report supports the concept of an association between acute pancreatitis and Crohn's disease.